Energy efficiency improvement for faculty of technical and vocational education building - Mohamad, Suhaimi (2014)
Energy efficiency becomes important matter due to correlate to sustainability and money. The ministry of Education Malaysia has urged all education center to conserved energy. Energy wastage tends to occur in Malaysian universities mainly due to inefficient use of energy and lack of awareness among building users. In this research, the researcher has analyse the building energy consumption and identify potential energy improvement that can be made in Faculty Technical and Vocational Education Universiti Tun Hussein Onn Malaysia. Suitable method to reduce energy consumption have been proposed without compromising user comfort in order to improve energy efficiency. The options of the proposed improvement method have been simulated using DIALUX and MATLAB/SIMULINK before the selection is done. This research have found that the most efficient lighting system for FPTV is using LED T8 replacement. The power factor correction have calculated and simulated. The researcher also has proposed the suitable method on management perspective to improve energy efficiency.